Vitamin D Supplementation in Alleviation of Oxidative Stress among Type 2 Diabetics (British Journal of Multidisciplinary and Advanced Studies, 2023)
Globally diabetes mellitus (T2DM) is a burning issue. Prediction of global estimation that the proportion of diabetes with adult will increase 69% for the year 2030. Hans Selye, the Canadian physiologist, was the first scientist to study the effects of psychological stress on the human body in 1936.Diabetic patients are in a state of high oxidative stress which leading to impaired glucose homeostasis, insulin insufficiency, and other complications.: A randomized controlled trial was conducted to see the effect of the vitamin D supplementation on oxidative stress in vitamin D deficientT2DM patients. In this study, a total of 124 T2DM patients were randomly enrolled, among them Treatment group 61 and placebo 63. In treatment group received 20,000IU vitamin D every 5thDay for three months in addition to regular treatment. Analysis of fasting   plasma glucose (FPG), Vitamin D 25(OH)2, malondialdehyde (MDA) and superoxide dismutase (SOD) have been estimated both at the time of study recruitment, at 6th weeks and after 12-weeks of vitamin D supplementation (endline). Present study showed after vitamin D supplementation, baseline mean FBG gradually significantly (P